Dietary Polyunsaturated Fat Intake in Relation to Glioma: A Case-Control Study. (3rd October 2018) - Dadfarma, Alireza; Shayanfar, Mehdi; Benisi-Kohansal, Sanaz; Mohammad-Shirazi, Minoo; Sharifi, Giuve; Hosseini, Saeed; Esmaillzadeh, Ahmad
Abstract: This study aimed to assess the association of dietary polyunsaturated fatty acid (PUFA) and risk of glioma among the Iranian population. A case-control study carried out among 128 newly diagnosed glioma adult patients with pathologically confirmed samples along with 256 sex- and age-matched controls. Dietary intake was examined by means of a validated semiquantitative food frequency questionnaire (FFQ). Total PUFA intake was computed by summing up dietary PUFAs from all food items in the questionnaire. Participants were categorized based on quartile cut-points of dietary PUFA intake. After taking into account the effect of age, sex and energy intake, individuals in the top quartile of PUFA intake were 77% less likely to have glioma than those in the bottom quartile (OR: 0.23; 95% CI: 0.11–0.48). Further adjustment for other potential variables strengthened the association. Additional controlling of nutrients did not alter the findings (OR: 0.19; 95% CI: 0.04–0.78). When we took into account the effect of body mass index (BMI), we found those in the highest quartile of PUFA intake has lower odds of glioma than those in the lowest (OR: 0.20; 95% CI: 0.05–0.84). We found dietary PUFA intake was inversely associated with risk of glioma in this case-control study on Iranian adults.